2013
DOI: 10.4028/www.scientific.net/amr.726-731.269
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Accumulation in Soil and Celery from a Long-Term Manure Applied Field Experiment

Abstract: A field experiment with six treatments was conducted from Apr. 2006 to Nov. 2008 to study the Cadmium (Cd) accumulation in soil and the effect on the plant uptake after a three years application with using different organic fertilizer. The six treatments were (1)Control (with no manure input), (2)Cattle compost, (3)Biogas residua, (4)Chicken compost (with low level input), (5)Chicken compost (with middle level input), (6)Chicken compost (with high level input). The treatments (2), (3) and (5) had the same tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Similar results were reported in a vegetable production field by Zhen et al [44], where total soil As content significantly decreased from 8.63 to 7.14 mg kg −1 , and total soil Cd significantly increased from 0.11 to 0.54 mg kg −1 after 15 years application of organic fertilizer that contained lower As content and higher Cd content that the initial soil, respectively. Previous studies also reported soil Cd accumulation following continuous application of organic fertilizer with higher Cd content than that of the initial soil [45,46,[59][60][61].…”
Section: As and CD Accumulation In Soilmentioning
confidence: 99%
“…Similar results were reported in a vegetable production field by Zhen et al [44], where total soil As content significantly decreased from 8.63 to 7.14 mg kg −1 , and total soil Cd significantly increased from 0.11 to 0.54 mg kg −1 after 15 years application of organic fertilizer that contained lower As content and higher Cd content that the initial soil, respectively. Previous studies also reported soil Cd accumulation following continuous application of organic fertilizer with higher Cd content than that of the initial soil [45,46,[59][60][61].…”
Section: As and CD Accumulation In Soilmentioning
confidence: 99%